Experimental and analytical investigation on metal damage suffered from simulated lightning currents - 刘亚坤;傅正财;刘全桢;刘宝全;Anirban GUHA (Plasma science & technology, 2017)
The damage of two typical metal materials, Al alloy 3003 and steel alloy Q235 B, subjected to four representative lightning current components are investigated by laboratory and analytical studies to provide fundamental data for lightning protection. The four lightning components simulating the natural lightning consist of the first return stroke, the continuing current of interval stroke, the long continuing current, and the subsequent stroke, with amplitudes 200 k A, 8 k A,400 A, and 100 k A, respectively. The damage depth and area suffered from different lightning components are measured by the ultrasonic scanning system. And the temperature rise is measured by the thermal imaging camera. The results show that, for both Al 3003 and steel Q235 B, the first return stroke component results in the largest damage area with damage depth0.02 mm uttermost. The long continuing current component leads to the deepest damage depth of 3.3 mm for Al 3003 and much higher temperature rise than other components. The correlation analysis between damage results and lightning parameters indicates that the damage depth has a positive correlation with charge transfer. The damage area is mainly determined by the current amplitude and the temperature rise increases linearly with the charge transfer larger.